Fragility of the marginal treatment effect - Paul J. Devereux (University College Dublin, UCD School of Economics, 2022)
Many interesting and important economic questions relate to the eects of binary treatments such as starting a college degree or participating in a job training program. The causal eects of these treatments are likely to be heterogeneous and recent research has emphasized the estimation of heterogeneous treatment eects, with a particular focus on Marginal Treatment Eects (MTEs). In this note, I describe why common methods of estimating MTEs of binary treatments can be very sensitive to omitted higher powers of covariates and demonstrate this using simple Monte Carlo simulations. I conclude by discussing approaches that may be useful for researchers to address this problem in practice.
Keywords: 330; Kausalanalyse; Monte-Carlo-Simulation; Schätztheorie